2020
DOI: 10.1038/s41598-020-65210-x
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of little auks foraging in various oceanographic features in a changing Arctic

Abstract: Using GpS-tracked individuals, we compared foraging ecology and reproductive output of a High-Arctic zooplanktivorous seabird, the little auk Alle alle, between three years differing in environmental conditions (sea surface temperature). Despite contrasting environmental conditions, average foraging fights distance and duration were generally similar in all studied years. Also, in all years foraging locations visited by the little auk parents during short trips (St, for chick provisioning) were significantly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 94 publications
2
32
1
Order By: Relevance
“…chicks age at fledging) in Hornsund and Magdalenefjorden colony (left panel), and bootstrap distribution of the inter-colony difference in mean day of the chicks fledging (right panel); the black vertical line at 0, being within the range of the permutated distribution, indicates no significant difference between the two colonies in the duration of the nesting period as long as it is necessary. Adjustment of parental behaviour by female little auks to current environmental conditions is consistent with the great flexibility of the species observed in various contexts related to foraging (Jakubas et al 2011(Jakubas et al , 2016(Jakubas et al , 2020Brown et al 2012;Gremillet et al 2012;Amélineau et al 2016).…”
Section: Discussionsupporting
confidence: 74%
“…chicks age at fledging) in Hornsund and Magdalenefjorden colony (left panel), and bootstrap distribution of the inter-colony difference in mean day of the chicks fledging (right panel); the black vertical line at 0, being within the range of the permutated distribution, indicates no significant difference between the two colonies in the duration of the nesting period as long as it is necessary. Adjustment of parental behaviour by female little auks to current environmental conditions is consistent with the great flexibility of the species observed in various contexts related to foraging (Jakubas et al 2011(Jakubas et al , 2016(Jakubas et al , 2020Brown et al 2012;Gremillet et al 2012;Amélineau et al 2016).…”
Section: Discussionsupporting
confidence: 74%
“…This could be especially the case for C. finmarchicus , whose demography was very similar between the fjord and shelf and which is probably mostly advected to the fjord. The small‐scale difference between fjord and shelf populations in demographic structure of C. glacialis, especially regarding the relative proportions between younger life stages and the most lipid‐rich fifth stage (CV), could be of great importance for CV‐selective predators such as little auks (Balazy et al., 2019; Jakubas et al., 2020; Welcker et al., 2009) and may explain why birds tend to forage on the shelf rather than in the fjord in the time window of their main feeding requirements (Jakubas et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the commonly observed difference in the size and thus the amount of lipids between C. finmarchicus and C. glacialis , the two species were believed to support different arctic food webs (Renaud et al., 2018; Weslawski et al., 2009). The decreased availability of C. glacialis is expected to affect the breeding success of the most numerous seabirds, little auks (Jakubas et al., 2020; Stempniewicz et al., 2007). However, the predicted higher abundance of C. finmarchicus in the Arctic (Reygondeau & Beaugrand, 2011; Slagstad et al., 2011) is expected to favor fish stocks (Falk‐Petersen et al., 2007; Renaud et al., 2018; Stempniewicz et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the latter group on terrestrial ecosystems is therefore much smaller compared to Little Auks because the guano deposited on the seabird cliffs is rapidly washed out to sea (Stempniewicz et al 2007). These results clearly indicate that the Little Auk Preference and specialization on a superior prey type that guarantees the best net energy gain (Weslawski et al 1999;Karnovsky et al 2003;Vogedes et al 2014;Møller et al 2018) Flexibility of foraging behaviour Spatio-temporal variation in environmental conditions in foraging areas (Jakubas et al , 2016(Jakubas et al , 2017(Jakubas et al , 2020Welcker et al 2009a, b;Harding et al 2009a;Kwasniewski et al 2010Kwasniewski et al , 2012Karnovsky et al 2011;Brown et al 2012;Grémillet et al 2012;Amélineau et al 2019) Predator-prey interaction Highly synchronized breeding, strong interrelationships with a limited number of predators (Stempniewicz 1995;Burnham 2005;Wojczulanis et al 2005;Jakubas and Wojczulanis-Jakubas 2010) Trade-off between the benefits of investment in current offspring and costs to future reproduction Long-lived, iteroparous species with low annual fecundity are less exposed to the risk of mortality during a given breeding attempt (Gębczyński et al 1996;…”
Section: Ecosystem Engineeringmentioning
confidence: 92%
“…Even where and when the preferred Arctic zooplankton is less abundant, they have been able to breed successfully with no negative consequences on chick survival, stress levels, or the body masses of adults and chicks (Kwasniewski et al 2010;Jakubas et al , 2017Grémillet et al 2012). However, some studies have reported serious consequences of suboptimal foraging conditions-a slower chick growth rate (Jakubas et al , 2020Kidawa et al 2015), a decrease in interannual survival rates of adult Little Auks (Hovinen et al 2014a) with a potentially strong effect on population dynamics and viability in such a long-lived species (Saether and Bakke 2000). It has been found that interannual changes in sea ice phenology and primary productivity pulses (affecting the transfer of biomass and energy through Arctic food webs) in Svalbard affected the breeding performance of Little Auks: chick survival decreased with the increasing time lag between the annual peaks of sea ice extent and primary production (Ramírez et al 2017).…”
Section: Indicator Of Environmental Changesmentioning
confidence: 99%